Mass-conserved ice sheet geometry of Pine Island Glacier, West Antarctica - Nias, Isabel (Polar Data Centre, Natural Environment Research Council, UK, 2018)
This gridded dataset provides geometry (ice thickness and bedrock topography) covering the Pine Island Glacier catchment. It has been created using the principle of mass conservation, given observed fields of velocity, surface elevation change and surface mass balance, together with sparse ice thickness data measured along airborne radar flight-lines. Previous ice flow modelling studies show that gridded geometry products that use traditional interpolation techniques (e.g. Bedmap2) can result in a spurious thickening tendency near the grounding line of Pine Island Glacier. Removing the cause of this thickening signal, in order to more accurately model ice flow dynamics, has been the motivation for creating a new geometry that is consistent with the conservation of mass.